Medication optimization according to the Fit fOR The Aged (FORTA) rules improves functional status in patients hospitalized for geriatric rehabilitation - Pazan, Farhad; Wehling, Martin; Weiß, Christel; Frohnhofen, Helmut (European geriatric medicine, 2023)
To analyze the impact of medication optimization according to the FORTA list on functional status in patients undergoing geriatric rehabilitation.
Online veröffentlicht: 19. April 2023
Gesehen am 08.07.2024